Kecemasan akademik mahasiswa dalam menghadapi ujian praktik laboratorium - Abdillah, Hadi; Rahayuwati, Laili; Yosep, Iyus (Holistik Jurnal Kesehatan, 2025)
Background: Academic anxiety is a common problem faced by students, especially in facing laboratory practical exams. This anxiety can affect students' performance in exams and potentially interfere with their academic results. Purpose: To describe the level of students' academic anxiety in laboratory practical exams. Method: Quantitative descriptive design and purposive sampling technique. The sample of this study consisted of 68 nursing students who faced a laboratory practical exam. Data collection was carried out using the second edition of the Cognitive Test Anxiety Scale (CTAS) questionnaire consisting of 24 statements regarding academic anxiety. Data analysis was carried out descriptively by calculating the frequency, percentage, and average score. Results: Most students had a moderate level of academic anxiety with an average score of 56.72. Further analysis revealed that this anxiety was more often experienced by students who entered college of their own accord. This academic anxiety was proven to affect student performance in the practical exam considering that the exam requires proper practical skills. Conclusion: Most respondents showed a moderate level of anxiety with an average score of 56.72, indicating that academic anxiety is a significant problem faced by students in higher education, especially in the nursing field. Suggestion: Further research can broaden its focus by exploring differences in academic anxiety levels in students from various majors or disciplines, as well as examining more specific factors that influence anxiety in practical exams.   Keywords: Academic Anxiety; Practical Exams; Students.   Pendahuluan: Kecemasan akademik adalah masalah yang sering dihadapi oleh mahasiswa, khususnya dalam menghadapi ujian praktik laboratorium. Kecemasan ini dapat memengaruhi kinerja mahasiswa dalam ujian dan berpotensi mengganggu hasil akademik mereka. Tujuan: Untuk menggambarkan tingkat kecemasan akademik mahasiswa dalam ujian praktik laboratorium. Metode: Desain deskriptif kuantitatif dan teknik sampling purposive. Sampel penelitian ini terdiri dari 68 mahasiswa keperawatan yang sedang menghadapi ujian praktik laboratorium. Data dikumpulkan menggunakan kuesioner Cognitive Test Anxiety Scale (CTAS) edisi kedua, terdiri dari 24 pernyataan mengenai kecemasan akademik. Data dianalisis secara deskriptif dengan menghitung frekuensi, persentase, dan skor rata-rata. Hasil: Sebagian besar mahasiswa memiliki tingkat kecemasan akademik yang sedang dengan skor rata-rata 56.72. Analisis lebih lanjut mengungkapkan bahwa kecemasan ini lebih sering dialami oleh mahasiswa yang masuk kuliah atas kemauan sendiri. Kecemasan akademik ini terbukti berpengaruh terhadap performa mahasiswa dalam ujian praktik, mengingat ujian tersebut memerlukan keterampilan praktis yang presisi. Simpulan: Sebagian besar responden menunjukkan tingkat kecemasan yang sedang dengan skor rata-rata 56.72, mengindikasikan bahwa kecemasan akademik merupakan masalah signifikan yang dihadapi mahasiswa dalam pendidikan tinggi, terutama di bidang keperawatan. Saran: Penelitian selanjutnya dapat memperluas fokusnya dengan mengeksplorasi perbedaan tingkat kecemasan akademik pada mahasiswa dari berbagai jurusan atau disiplin ilmu, serta mengkaji faktor-faktor yang lebih spesifik yang memengaruhi kecemasan pada ujian praktik.   Kata Kunci: Kecemasan Akademik; Mahasiswa; Ujian Praktik.